Validation of claims‐based algorithms to identify non‐live birth outcomes. Issue 4 (30th November 2022) - Zhu, Yanmin; Bateman, Brian T.; Hernandez‐Diaz, Sonia; Gray, Kathryn J.; Straub, Loreen; Reimers, Rebecca M.; Manning‐Geist, Beryl; Yoselevsky, Elizabeth; Taylor, Lockwood G.; Ouellet‐Hellstrom, Rita; Ma, Yong; Qiang, Yandong; et al.
Abstract: Purpose: Perinatal epidemiology studies using healthcare utilization databases are often restricted to live births, largely due to the lack of established algorithms to identify non‐live births. The study objective was to develop and validate claims‐based algorithms for the ascertainment of non‐live births. Methods: Using the Mass General Brigham Research Patient Data Registry 2000–2014, we assembled a cohort of women enrolled in Medicaid with a non‐live birth. Based on ≥1 inpatient or ≥2 outpatient diagnosis/procedure codes, we identified and randomly sampled 100 potential stillbirth, spontaneous abortion, and termination cases each. For the secondary definitions, we excluded cases with codes for other pregnancy outcomes within ±5 days of the outcome of interest and relaxed the definitions for spontaneous abortion and termination by allowing cases with one outpatient diagnosis only. Cases were adjudicated based on medical chart review. We estimated the positive predictive value (PPV) for each outcome. Results: The PPV was 71.0% (95% CI, 61.1–79.6) for stillbirth; 79.0% (69.7–86.5) for spontaneous abortion, and 93.0% (86.1–97.1) for termination. When excluding cases with adjacent codes for other pregnancy outcomes and further relaxing the definition, the PPV increased to 80.6% (69.5–88.9) for stillbirth, 86.6% (80.5–91.3) for spontaneous abortion and 94.9% (91.1–97.4) for termination. The PPV for the composite outcome using the relaxed definition was 94.4% (92.3–96.1). Conclusions: Our findings suggest non‐live birth outcomes can be identified in a valid manner in epidemiological studies based on healthcare utilization databases.